Electroacupuncture of Baihui and Shenting ameliorates cognitive deficits via Pten/Akt pathway in a rat cerebral ischemia injury model - Su, Kaiqi; Hao, Wenxue; Lv, Zhuan; Wu, Mingli; Li, Jieying; Hu, Yanchao; Zhang, Zhenhua; Gao, Jing; Feng, Xiaodong (Frontiers in Neurology, 2022)
Cerebral ischemia stroke is a huge threat to the health and life of many people. Electro-acupuncture (EA) at Baihui (GV20) and Shenting (GV24) acupoints can notably alleviate cerebral ischemia/reperfusion injury (CIRI). However, the molecular basis underlying the effectiveness of EA at GV20 and GV24 acupoints for CIRI remains largely unknown. In this study, we demonstrated that EA treatment at GV20 and GV24 acupoints markedly alleviated middle cerebral artery occlusion/reperfusion (MCAO/R)-induced rat cognitive deficits and cerebral infarction. Proteomics analysis revealed that 195 proteins were differentially expressed in hippocampus tissues of rats after MCAO/R surgery, and 218 proteins were differentially expressed in MCAO/R rats after EA treatment at GV20 and GV24 acupoints. Moreover, 62 proteins with converse alteration trends in MCAO/R versus sham and EA versus MCAO/R groups were screened out. These proteins might be implicated in EA-mediated protective effect against MCAO/R-induced cerebral injury. Also, 39 dysregulated proteins after MCAO/R surgery and 40 dysregulated proteins after EA treatment were identified to be related to brain and nerve development based on GO enrichment analysis of differentially expressed proteins. Next, protein-protein interaction networks of the 39 dysregulated proteins after MCAO/R surgery and 40 dysregulated proteins after EA treatment were established by the String database. Results suggested that Pten/Akt pathway-related proteins (e.g. Akt3, Pten, and Efnb2) might play vital roles in regulating EA-mediated protective effects against MCAO/R-induced brain and nerve injury. In conclusion, multiple proteins related to the protective effect of EA at GV20 and GV24 acupoints against CIRI were identified in our study.